2022
DOI: 10.1155/2022/5544665
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Soybean Genotypes for Waterlogging Stress Tolerance and Understanding the Physiological Mechanisms

Abstract: Waterlogging is a common form of abiotic stress that severely impedes global soybean production. Targeting this issue, an experiment was carried out at Sher-e-Bangla Agricultural University during August–November 2019 to screen out the waterlogging tolerance and yield performances of selected soybean genotypes. The experiment was laid out in a completely randomized design (CRD) with three replications consisting of 2 water levels (control and waterlogging) and 12 genotypes (Sohag, BARI Soybean-5, BINAsoybean-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…Azizi, et al [29] explained a significantly lower leaf RWC in flooded Populus euphratica by limited water uptake by the plant root system. A similar decline in leaf water content during flooding stress was seen in sorghum and soybean [30,31].…”
Section: Plant Height Relative Water Content (Rwc) and Electrolyte Le...supporting
confidence: 66%
“…Azizi, et al [29] explained a significantly lower leaf RWC in flooded Populus euphratica by limited water uptake by the plant root system. A similar decline in leaf water content during flooding stress was seen in sorghum and soybean [30,31].…”
Section: Plant Height Relative Water Content (Rwc) and Electrolyte Le...supporting
confidence: 66%
“…Flood stress reduced the protein concentration and deactivated APX in submerged soybean seedlings compared to the control, as Damanik et al (2016) studied earlier. Sathi et al (2022) observed that flooding stress increased the mortality rate and electrolyte leakage in soybean. The plant showed a delayed flowing pattern and maturity compared to control conditions (Sathi et al, 2022).…”
Section: Effects Of Flooding Stress On Soybeanmentioning
confidence: 97%
“…Sathi et al (2022) observed that flooding stress increased the mortality rate and electrolyte leakage in soybean. The plant showed a delayed flowing pattern and maturity compared to control conditions (Sathi et al, 2022). Flood stress decreases the rate of respiration in roots (Wegner, 2010), and causes a decline in energy resources, loss of carbon, and deposition of noxious compounds, mainly lactate (Tamang et al, 2014).…”
Section: Effects Of Flooding Stress On Soybeanmentioning
confidence: 97%
See 2 more Smart Citations